The Blood of Strangers : Stories From Emergency Medicine. - Huyler, Frank (University of California Press, 1999)
Reminiscent of Chekhov's stories, The Blood of Strangers is a visceral portrayal of a physician's encounters with the highly charged world of an emergency room. In this collection of spare and elegant stories, Dr. Frank Huyler reveals a side of medicine where small moments--the intricacy of suturing a facial wound, the bath a patient receives from her husband and daughter--interweave with the lives and deaths of the desperately sick and injured.